Employability within South African businesses in the 4IR era: The impacts of abilities, self-efficacy, and work-integrated learning effectiveness - Masase Mageza-Mokhethi; Foluso Philip Adekanmbi (Problems and Perspectives in Management)
The South African education sector and businesses are concerned about whether higher education institutions could meet the demands and expectations of the labor market in the context of the fourth industrial revolution (4IR). Hence, it becomes essential to examine the perceived employability of work-integrated learning graduates within businesses in the context of the 4IR. This study seeks to examine employees’ perceptions of the influence of graduates’ abilities, self-efficacy, and effectiveness of work-integrated learning on their employability in the context of 4IR. The sample was obtained from employees from four South African firms (Syntech Ltd, Centrevo Ltd, Outsurance Ltd, and First National Bank Plc) in the information technology, sales, insurance, and banking industries. This study used a cross-sectional questionnaire. Of the 200 surveys randomly floated, 196 were fitting for scrutiny, cleaning, and analysis. Consequently, this study found that South African employees perceive graduates’ employability as being significantly and positively influenced by their abilities (β = .802, p < .001), self-efficacy (β = .815, p < .001), and work-integrated learning (β = .864, p < .001). In the third-step model, these three factors substantially impacted graduates’ employability more than other likely combination matrices. Therefore, 97% of South African graduates are perceived employable in the fourth industrial revolution era due to their abilities, self-efficacy, and participation in work-integrated learning. This investigation concludes that in the 4IR, the employability of South African graduates is mainly impacted by their self-efficacy, abilities, and the effectiveness of work-integrated learning. AcknowledgmentsWe thank the Department of Industrial Psychology and People Management at the University of Johannesburg’s College of Business and Economics for funding this study and its publication.